GRB 221009A with an Unconventional Precursor: A Typical Two-stage Collapsar Scenario? - Song, Xin-Ying; Zhang, Shuang-Nan (The Astrophysical journal, 2023)
As the brightest gamma-ray burst (GRB) ever detected, GRB 221009A may offer a chance that reveals some interesting features that are hidden in those bursts that are not so bright. There seems to be a very weak emission with a flux of 10 −8 ∼ 10 −7 erg cm −2 s −1 between the first pulse ( T 0 ∼ T 0 + 50 s; T 0 is the trigger time) and the main burst (which appears from T 0 + 180 s). Thus, the gap time between them is not really quiescent, and the first pulse could be taken as an unconventional precursor, which may provide a peculiar case study for GRB precursor phenomena. A two-stage collapsar scenario is proposed as the most likely origin for this burst. In this model, the jet for the precursor is produced during the initial core-collapse phase, and should be weak enough not to disrupt the star when it breaks out of the envelope, so that the fallback accretion process and the forming of the disk could continue. We present an approach in which the duration and flux both provide constraints on the luminosity ( L j ) and the Lorentz factor at the breakout time (Γ b ) of this weak jet. The estimated L j ≲ 10 49 erg s −1 and Γ b has an order of 10, which are well consistent with the theoretical prediction. Besides, the weak emission in the gap time could be interpreted as an MHD outflow due to a magnetically driven wind during the period from the proto-neutron-star phase to the forming of the accretion disk in this scenario.